Imported inflation and monetary policy. A reply - SCOTT, I.O. Jr.; SCHMIDT, W.E. (PSL Quarterly Review, 2014)
<!–[if gte mso 9]> 72 1024x768 <![endif]–> In this brief rejoinder the authors respond to P.M. Oppenheimer’s criticism of their article Imported inflation and monetary policy. The authors reject Oppenheimer’s criticism of the data they use as well as the theoretical objections he raised. They argue that while the imported-inflation argument says monetary restraint will not work, Oppenheimer is saying that the authorities did not want it to work, a very different matter. JEL: E31, E42, E52 <!–[if gte mso 9]> Normal 0 14 <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; –> <!–[endif] –>